Knowledge, attitudes, and perceptions of MSM Towards ED-PrEP across five districts in South Africa - Mapungwana, Pheyiye; Mapungwana, P.; Chadyiwa, Martha (Orapuh Journal, 2025)
Introduction Men who have sex with men (MSM) are at higher risk of contracting HIV. Consensual anal sex (CAS) is the highest-risk sexual act for HIV transmission. All conceivable HIV prevention options ought to be made available, coupled with demand creation strategies intended to enhance the adoption and use of these interventions, to reduce HIV transmission among MSM. A unique and scientifically supported approach to overcoming obstacles to MSM adoption of current HIV prevention strategies (daily PrEP, male circumcision, condom use) is event-driven PrEP (ED-PrEP). Purpose This study investigates the knowledge, attitudes, and perceptions (KAP) of MSM towards event-driven PrEP (ED-PrEP) and explores relationships between socio-demographic characteristics, sexual risk profiles, and willingness to use ED-PrEP across five districts in South Africa. Methods A cross-sectional study was conducted with 295 MSM participants recruited from drop-in clinics across five districts in South Africa between April and June 2023. A structured online questionnaire assessed demographic information, HIV risk behaviours, and KAP regarding ED-PrEP. Descriptive statistics were calculated, and logistic regression analyses were performed to identify predictors of knowledge and attitudes towards ED-PrEP. Statistical significance was set at p < 0.05. Results The study found that 71.9% of participants had good knowledge of ED-PrEP, while 58% expressed a positive attitude towards its use. Logistic regression analysis revealed that sexual orientation (OR = 2.5, p = 0.03), perceived risk of acquiring HIV (OR = 3.8, p < 0.001), and education level (OR = 2.2, p = 0.002) were significant predictors of willingness to recommend ED-PrEP. Conclusion The findings highlight a high level of awareness and willingness to use ED-PrEP among MSM, particularly in urban districts. Targeted public health campaigns are recommended to enhance understanding and acceptance of ED-PrEP by addressing misconceptions and providing tailored information to improve uptake and adherence, ultimately contributing to HIV epidemic control.